Corpus linguistics for English for academic purposes - Viana, Vander; O'Boyle, Aisling (Routledge, 2021)
"This book shows how corpus analyses can enhance students', practitioners' and researchers' knowledge of academic language. The book provides a reader-friendly discussion of the key concepts, practices and research applications of corpus linguistics which are relevant to the EAP community. Corpus Linguistics for English for Academic Purposes is an essential book for EAP students, practitioners and researchers who wish to develop corpus analytical skills to support their learning, teaching and research practice. It is equally important to novice corpus linguists who wish to find out how they can contribute to the ever-expanding area of EAP."- Resumé vydavatel
Keywords: angličtina; studium a výuka; korpusová lingvistika; vysokoškolské studium; English language; study and teaching; corpus linguistics; college study; elektronické knihy; monografie; electronic books; monographs